Tat'biq Lu'bah Shunduq Al- Asya Fi Ta'lim Maharatul Kalam lada Tullab Al Faslun Al- Asyir Fi Madrasah At Tsanawiyah Al Islamiyah Al Hukumiyah At - Ilmi Hayati; Rita Febrianta; Nurhasnah Nurhasnah; Hurriyatus Sa'diyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Research Summary This thesis was prepared by Ilm Hayati, registration number: (2219042). Department of Arabic Language Education, College of Education and Educational Sciences, University of Syeikh Muhammad DJamil DJamik Bukittinggi State Islamic State Bukittinggi, on the topic “Application of the Object Box Game to improve the speaking skill of students at the Second Government Islamic Secondary School in Man 2 Madina Natal. The problem in this school is the following: lack of use of the medium in teaching the Arabic language, lack of ability to speak skill among students in secondary schoolThe Second Islamic Government of Mandailing Natal, Arabic language teaching that is monotonous, lack of students' desire to learn the Arabic language. As for the methodology of the research in this research, using the experimental and counting the research community, the total number =77,the number of students in the experimental class is 36, students. Then the research tools are observation, testing, and documentation. ability, speaking skill, students in the tenth chapter between teaching the game of the box of things was applied and the game of the box of things was applied in teaching the Arabic language and its results are (Ho) rejected and (Ha) allowed.